Two steps forward one step back: what shapes the process of EU enlargement in South-Eastern Europe?. Issue 7 (9th November 2016) - Schwarz, Oliver
Abstract: Which factors shape the process of EU enlargement in South-Eastern Europe? This question continues to be a puzzling subject of scholarly debate. A set of hypotheses can be derived from current literature on EU enlargement. Broadly speaking, these hypotheses fall into two general categories: internal and external factors. Building on these factors, the analysis elaborates on the idea of different paths of EU enlargement, adopting a qualitative comparative perspective. More specifically, the study applies fuzzy-set QCA to eight candidate states from South-Eastern Europe. The results show that the factor of political transformation is a necessary condition for EU enlargement in South-Eastern Europe. However, political transformation is not individually sufficient for the outcome of enlargement, but only in conjunction with other factors. The results also demonstrate that what explains the lack of enlargement process is not automatically the negation of the conditions that explain progress in enlargement.